2021
DOI: 10.1039/d1ta02769g
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on the synthesis and oxygen reduction applications of Fe-based single-atom and double-atom catalysts

Abstract: Single-atom and double-atom catalysts have emerged as new frontiers in many fields due to their high atom-utilization efficiency, excellent catalytic properties and good durability. In this decade, Fe-based atomic catalysts...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(71 citation statements)
references
References 197 publications
(185 reference statements)
0
71
0
Order By: Relevance
“…By optimizing the electron cloud density near the metal atom centers with the electron transfer 50 from boron, 51 sulfur (S), or phosphor(P) to metal, the incorporation of light heteroatoms provides a promising artificial synthesis approach for nitrogen fixation to improve NRR performance. Chu et al 52 .…”
Section: Monometallic Fe‐based Catalysts For the Nrrmentioning
confidence: 99%
“…By optimizing the electron cloud density near the metal atom centers with the electron transfer 50 from boron, 51 sulfur (S), or phosphor(P) to metal, the incorporation of light heteroatoms provides a promising artificial synthesis approach for nitrogen fixation to improve NRR performance. Chu et al 52 .…”
Section: Monometallic Fe‐based Catalysts For the Nrrmentioning
confidence: 99%
“…Mixing of isolated Fe and Co single atomic sites has been shown to improve the catalytic ability via activating O 2 [41] . At present, several studies have also found that Fe−Co synergistic sites can prolong O−O bond and reduce the energy barrier of O−O breaking [42] . Wang et al.…”
Section: Heteronuclear Dacs With Two Different Metal Atomsmentioning
confidence: 99%
“…[41] At present, several studies have also found that FeÀ Co synergistic sites can prolong OÀ O bond and reduce the energy barrier of OÀ O breaking. [42] Wang et al successfully prepared Fe and Co atoms embedded in N-doped porous carbon [(Fe,Co)/NÀ C] by a hostguest strategy (Figure 2c,d). [43] (Fe,Co)/NÀ C exhibited a halfwave potential of 0.86 V vs. RHE (Figure 2e) and negligible activity reduction during 50000 cycles for electrocatalytic oxygen reduction in acidic electrolytes.…”
Section: Oxygen Reduction Reactionmentioning
confidence: 99%
“…10–12 Significantly, the highly unsaturated coordination bonds in N-doped conductive carbon supports could coordinate with various metals, leading to nearly 100% efficiency of atomic utilization in the M–N x –C system, which stimulates a strong quantum effect. 13,14 Therefore, the earth-abundant transition metals anchored on N-doped carbon substrates, especially in the form of M–N x –C materials, 15–17 could show unexpected electrocatalytic activity and promising stability towards the ORR. However, such materials suffer from limited active sites because of their undisciplinable low atomic densities, and the isolated metal atoms can be deactivated because of aggregation or leaching in the ORR catalytic process.…”
Section: Introductionmentioning
confidence: 99%